Requirement Engineering for the Development of Agent Oriented Data Warehouse - Bharadwaj, S; Goyal, AK (International Journal of Computer Sciences and Engineering, 2025)
A software system design was said to be succeeded only when it satisfies the purpose for which it was intended. Requirement Engineering (RE) is the progression of determining that purpose, by recognizing stakeholders and their desires and recording these in a form that is adaptable to analysis, communication and implementation. Agent–oriented perceptions are growing very popular in software engineering as demonstrating frameworks for RE. On the other hand, Data Warehouse (DW) is a field of computer science that is used to capture the historical information to provide decisions to be taken by the management. In this paper, we used a blend of these technologies with Agent-Goal-Decision-Information (AGDI) model for the RE of DW. Based on the proposed AGDI model, a new RE approach has been proposed.